Workplace wellness : an analysis of firm and individual factors in the least healthy sectors - COÊLHO, André Luiz Ribeiro Coutinho Berardo de Moraes (2023)
This thesis aims to analyze how individual and firm factors influence a person to work in the least healthy sectors using firms’ and workers’ observed and non-observed characteristics through a Discrete Choice Model. The main idea is to understand how individual and firm factors impact a person to work in the least healthy sector conditional on individuals’ and firms’ characteristics using unique combined data through individual CPF (Individual Taxpayer Registry) from the SES-PE 2020 (Pernambuco State Health Department) and RAIS 2019 (Annual List of Social), containing latitude and longitude where each person lives and works. The State of Pernambuco was one of the states with the most cases in Brazil, fifth in the nation, with 25,760 cases as of May 24, 2020, and the model is estimated for its capital, Recife. The model is first estimated for the essential sectors. Thus, men present a higher chance of working in the essential sectors, and there is a lower incidence of an older or non-white individual being employed in these sectors. A higher minimum wage attracts more workers, and there is also a higher incidence of working hours and job tenure among employees in the essential sectors. The model is then estimated by dividing the economic sectors into two groups, the Least Healthy and Other Sectors. First, the least healthy group is defined by the highest number of people who tested positive for COVID-19 among all economic sectors. Second, it is defined by the economic sectors that are considered the essential sectors, the ones that did not experience lockdown. The model estimated with the latter definition best fits the data. The current thesis's importance is to contribute to how the workers' and firms’ characteristics affect an individual working in the least healthy sectors. The research advances because COVID-19 is an exogenous factor that helps expose which economic sectors the individuals work in are the least healthy. Public policies can be directed to promote equal opportunities through racial quotas, gender equality, income distribution, investment in the health system and education, public transportation, and sanitation. The informal sector is not considered.